Economic-Environment-Energy (3E) objective-driven integrated municipal waste management under deep complexities – A novel multi-objective approach. (December 2022) - Liang, Xiaolin; Ji, Ling; Xie, Yulei; Huang, Guohe
Highlights: WtE technologies compatible with recycling are integrated into the MSW system. Multi-objective-driven integrated MSW management is optimized to achieve sustainable goals. An interval-valued fuzzy linear programming method is developed to address uncertainties. The subsidy is still required to encourage anaerobic digestion from the environmental aspect. Abstract: Waste-to-energy technologies compatible with recycling are promising solutions for sustainable municipal waste management from both economic and environmental perspectives. This study focuses on the economic-environment-energy (3E) objective-driven integrated waste management optimization problems under deep complexities. A novel multi-objective programming model is developed to assist the optimal decision-making with the consideration of system profit, greenhouse gas emission, and energy recovery simultaneously. Besides, it advances existing optimization methods by incorporating interval-valued fuzzy numbers to tackle the ambiguity and the essential fuzziness in experts' judgment. It was verified by a case study from an urban district of Beijing, China. The optimum waste treatment facility planning and waste stream allocation strategies with multi-objective tradeoffs were obtained to support decision-making considering different preferences of importance ranking. In general, incineration and anaerobic digestion would be the main technologies for waste disposal in the study area. Recycling would be greatly encouraged when pursuing more economic profits and greenhouse gas emission reduction. With withdrawing the subsidy in the future, the investment in anaerobic digestion would become less attractive. Meanwhile, the landfill with gas recovery would even become economically infeasible if there is no further reduction in cost. In addition, waste source separation is also a crucial factor for successful integrated waste management. It is suggested that a proper government subsidy and public participation in waste source separation would guarantee the sustainable development of the integrated waste management system. Graphical abstract: Image, graphical abstract